Interfacial Activity and Acute Toxicity of Surfactants to Aquatic Animals - Oya, Masaru; Takada, Noriko; Kobayashi, Takeshi (Journal of Water and Environment Technology, 2025)
The environmental effects of surfactants have been studied from various perspectives, such as aquatic toxicity and biodegradability. Surfactants exhibit different physiochemical properties depending on their structural characteristics. This review discusses the relationship between surface tension and the interfacial activity of the most widely used surfactants (anionic and nonionic surfactants). This relationship is typically observed when surfactants and test animals used for toxicity test are fixed. First, this review discusses previous studies on the toxicity and surface tension as an interfacial property of surfactants. Then, an effect of water hardness, which is the most influential factor on both the toxicity and interfacial activity of anionic surfactants, is discussed using surface tension as an indicator. Thereafter, the change in the toxicity of anionic surfactants under different conditions are highlighted: different water hardness and adsorbent, primary biodegradation of linear alkylbenzene sulfonate, low water hardness in the presence of fatty acid salts, different water hardness for binary surfactant mixtures. Additionally, the review highlights the relation of toxicity changes and the surface tension change under each condition. This review aims to provide a better understanding of the toxicity of surfactants from the perspective of interfacial activity.